Revolutionizing B2B procurement: Digital transformation at PT Sadang Jaya - Riady, Clive; Tony, Tony (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The rapid pace of digital transformation presents both challenges and opportunities for businesses globally, especially in the realm of Business-to-Business (B2B) order management. Many Indonesian companies continue to rely on outdated, manual processes, leading to inefficiencies and scalability issues. This study explores how PT Sadang Jaya, a food production company in the Indonesian market, tackled these challenges through the strategic implementation of a custom-built B2B order management system using Angular, Express.js, PostgreSQL, and Agile methodology. PT Sadang Jaya, despite its strong market reputation, encountered difficulties in managing orders efficiently as the company grew and the number of distributors increased. The manual order management process, conducted through WhatsApp or phone calls, became increasingly inefficient and prone to errors, resulting in irregular order queues and increased risk of recording errors. To overcome these challenges, the company recognized the need for a B2B eCommerce system that could streamline transactions between PT Sadang Jaya and its distributors. This thesis aims to design and develop a web-based online ordering application that not only reduces recording errors but also accelerates the order fulfillment process and strengthens business relationships with distributors. The results of User Acceptance Testing (UAT) demonstrate the successful completion of all test cases without any blocking issues, comprehensively verifying the system's functionality, including order management and distributor interaction. The implementation of this system is anticipated to capitalize on the immense potential of B2B eCommerce, enabling PT Sadang Jaya to broaden its market reach and elevate distributor satisfaction through more integrated and responsive services.